Unique Components of Malaysia Counsellor Performance Indicator (M-CPI) : A Tool to Measure the Performance of Counsellors in Malaysia - Nor Mazlina, Ghazali; Aqilah, Yusoff; Wan Marzuki, Wan Jaafar; Salleh, Amat; Edris, Aden; Azzahrah, Anuar (Iran University of Science and Technology, 2023)
The research aimed to determine the best components of Malaysia-Counsellor Performance Indicator in measuring the counsellor’s performance in Malaysia. This is the first development phase of the MCPI. This study involved two types of research designs; quantitative and qualitative approaches (Mixed Method). The quantitative data has been obtained from 102 respondents and interview with eight (8) counsellors from different settings. A stratified random sampling technique was utilized to select the respondent and proportional stratification was used to determine the sample size of each stratum. A Need Assessment questionnaire has been developed by the researchers as well as the protocol interview. These two instruments were developed based on the literature reviews of previous instruments that have been invented from the Western perspective to measure the performance and competency of counsellors. The results of the study were analysed using descriptive analysis and thematic analysis. Findings have shown that the majority of counsellors possessed knowledge and skills in conducting counselling sessions. Most counsellors in the study demonstrated good interpersonal relationships, interaction, multicultural and religiosity and ethics and professionalism. Through this study, to measure the performance of counsellors, the researchers have found that they must equip themselves with knowledge, skill, interpersonal relationship, interaction, multicultural and religiosity and ethics and professionalism aspects. Based on the interview data, there were new components that have been identified to be added to the Malaysia Counsellor Performance Indicator (M-CPI) which include knowledge (theoretical and knowledge transfer), skills (case management, practical skills and academic/professional writing), interpersonal relationship and interaction, cultural and religiosity, professional roles and expertise, ethics and legality, attitudes and personality, referral and articulate philosophy of the profession. In futur